FEATURES OF BILATERAL BREAST CANCER NODAL METASTASIS - Ye. A. Fesik; N. V. Krakhmal; M. V. Zaviyalova; Ye. M. Slonimskaya; S. V. Vtoryshin; V. M. Perelmuter (Бюллетень сибирской медицины, 2014)
This article focuses on issues related to the identification and investigation of the lymph node metastases with bilateral breast cancer. The presence of metastases in the lymph nodes determines the stage of the disease, and introducing a form of tumor progression, characterizes the course and prognosis for the future in a specific patient. Thus, the identification of possible morphological and immunohistochemical characteristics of the tumor tissue and their comparison with the frequency and severity of regional lymph nodes would help to solve the problem of the identification of prognostic factors and markers associated with the risk of nodal metastasis in bilateral breast cancer. This work is relevant due to the fact that the literature on this issue to date are treated ambiguously, and answers to many questions, unfortunately, no.The authors performed a morphological study of the tumor tissue from 600 patients suffering from unilateral and bilateral breast cancer. To avoid false results were studied only cases corresponding to the histological type of invasive carcinoma of non-specific type. The study found that a greater number and a greater percentage of the affected lymph node metastases were observed in patients with bilaterally synchronous tumors. The patients of this group of metastatic lymph nodes was detected more frequently in the presence of infiltrative component of three or more types of structures with the presence of these discrete groups of tumor cells, and the observed maximum degree of inflammatory infiltration of the tumor stroma. In the group of patients with unilateral breast cancer nodal metastasis often detects when triple negative molecular genetic type of the lesion, with large amounts of tumor site, in the presence of infiltrative component of three or more types of structures with the obligatory presence of these microalveolar structures and discretely spaced groups of tumor cells and the highest severity of hyalinosis of the stroma.The observed features of nodal metastasis associated with the morphological characteristics of the tumor tissue, may act as prognostic markers in determining the risk of lymph node metastases in women with bilateral breast cancer, which would have a significant aid in determining the prognosis of an individual patient, and, therefore, mean individual approach to the tactics of treatment of such patients.